1987
DOI: 10.1093/oxfordjournals.eurheartj.a062322
|View full text |Cite
|
Sign up to set email alerts
|

International differences in coronary heart disease mortality and consumption of fish and other foodstuffs

Abstract: The relationship between fish consumption and coronary heart disease mortality was investigated using data on foodstuff consumption and mortality from 21 countries. A moderate negative association was found which appeared stable over different periods. This association disappeared when the effects of other foodstuffs were controlled for in multiple regression analysis. One feature to emerge was the anomalous position of Japan in consumption of several foodstuffs. Inclusive or exclusion of this country from reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…In Zutphen, a Dutch area included in the classic Seven Countries Study, an inverse correlation between fish consumption and CAD was reported in middle-aged men during 20 years of follow up 28 . A similar inverse correlation between heart disease and fish consumption in Caucasian populations was reported by some [29][30][31][32][33][34] , but not by other investigators 23,[35][36][37][38][39][40] . In the Health Professionals Follow-up Study there was an unexplained increased risk of coronary artery bypass surgery grafting in men with higher fish consumption 40 .…”
Section: Primary Prevention Of Cadsupporting
confidence: 84%
“…In Zutphen, a Dutch area included in the classic Seven Countries Study, an inverse correlation between fish consumption and CAD was reported in middle-aged men during 20 years of follow up 28 . A similar inverse correlation between heart disease and fish consumption in Caucasian populations was reported by some [29][30][31][32][33][34] , but not by other investigators 23,[35][36][37][38][39][40] . In the Health Professionals Follow-up Study there was an unexplained increased risk of coronary artery bypass surgery grafting in men with higher fish consumption 40 .…”
Section: Primary Prevention Of Cadsupporting
confidence: 84%
“…Kromhout et al (1989) quantitated ''fish'' consumption through home observers in two villages, one in Japan's interior (93g/day; n ¼ 24) F the other on Japan's coastline (207 g/day, n ¼ 9). Crombi et al (1987) reported Japanese ''fish'' consumption between 1967 and 1969 to be about 100 g/day.…”
Section: Seafood Consumption Ratesmentioning
confidence: 99%
“…Interestingly, during this time period the incidence of fatal coronary events also showed a fourfold increase. Epidemiologic observations in Greenland Eskimos and other populations with a traditionally high intake of fish rich in n-3 fatty acids have shown a low incidence of cardiovascular and the other diseases observed with increasing frequency in Western communities [16,22]. The examination of their plasma fatty acids revealed a very low percentage of AA, which is only about 20% of that found in members of Western communities [12].…”
Section: Possible Long Range Effects Of the Uptake Of Increased Amounmentioning
confidence: 99%